Postpartum depression and its correlates: a cross-sectional study in southeast Iran - Mohammad Ali Zakeri; Somaye Khoram; Gholamreza Bazmandegan; Fatemeh Ghaedi-Heidari; Batol Talebi; Najmeh Ramezani; Fatemeh Ahmadi; Zahra Kamiab; Mahlagha Dehghan (BMC, 2022)
Abstract Background Postpartum depression has a negative impact on both infants and women. This study aimed to determine the correlates of postpartum depression in women in southern Iran. Methods This cross-sectional study was performed on 186 mothers who had recently given birth to a baby. Data were collected using the demographic form, Quality of Prenatal Care Questionnaire, Edinburgh Postnatal Depression Scale (EPDS), Depression, Anxiety and Stress Scale-21 items (DASS-21) 3 days after delivery and EPDS and DASS-21 6 months after childbirth. Results Postpartum depression (PPD) was 24.2% and 3.2% 3 days and 6 months after delivery, respectively. Anxiety, Prenatal Care Quality and educational level predicted 34.0% of the variance of PPD 3 days after delivery (R2 = 34.0%). Anxiety, type of delivery, and stress predicted 24% of the variance of PPD 6 months after delivery (R2 = 24.0%). Conclusions With an increase in stress and anxiety and a reduction in the quality of prenatal care, the risk of postpartum depression increases. Therefore, attention to the quality of prenatal care and postpartum stress and anxiety should be carefully evaluated to prevent PPD. Psychological support and interventions are recommended to promote the mental health of women before and after childbirth.